If It’s Broke, Fix It: Fixing Fixation - Carpenter, Megan M. (The Columbia Journal of Law & the Arts, 2016)
The fixation requirement, once an intended instrument for added flexibility in copyrightability, has become an unworkable standard under modern copyright law. The last twenty-five years have witnessed a dramatic expansion in creative media. Developments in both digital media and contemporary art have challenged what it means to be fixed, and cases dealing with these works reveal how inapposite current interpretations of fixation are for these forms of expression. Yet, getting fixation “right” is important, for it is often the juridical threshold over which idea becomes expression. Thus, we must enable fixation to help define the parameters of creative expression while not discriminating against dynamic and digital works. In previous work, Steven Hetcher and I have identified problems with the fixation requirement as it applies to modern creative expression and have argued for changes that would amend the fixation requirement to better function in the modern era.1 This Essay furthers that argument. As part of the Kernochan Center Symposium, “Copyright Outside the Box,” I argued that the transitory duration exclusion for copyrightability should be stricken from the definition of fixation to better enable it to reflect the parameters of modern creative expression. Agnieszka Kurant’s art serves as an example of this need for change. Removing the exclusion for transitory works, while maintaining the stability requirement, would retain the essence of the definition of fixation under the Copyright Act but enable application to modern forms of creative expression, including both contemporary art and digital works.